Atomic-scale characterization and modeling of 60° dislocations in a high-entropy alloy. (15th May 2016) - Smith, T.M.; Hooshmand, M.S.; Esser, B.D.; Otto, F.; McComb, D.W.; George, E.P.; Ghazisaeidi, M.; Mills, M.J.
Abstract: High-entropy alloys (HEAs) are an exciting new class of multi-component alloys some of which have unusual and remarkable properties. As of yet, little is understood about dislocation core structure and stacking fault energies in these alloys. For this study, a five-component, equiatomic alloy (CrMnFeCoNi) was deformed to 5% plastic strain at room temperature. Post-test observations using diffraction contrast scanning transmission electron microscopy (DC-STEM) analysis provide evidence for numerous planar slip bands composed of ½<110> dislocations. More detailed analyses of dislocation separation distances were performed using high-order diffraction vector DC-STEM and atomic resolution high angle annular dark field (HAADF) STEM on ½<110> dislocations in 60° orientation. Large variations in dissociation distances are found, leading to the concept of a local stacking fault energy (SFE). This finding is supported through embedded-atom-method (EAM) calculations of a model, concentrated, three-element solid solution. For the first time, the Nye tensor and center of symmetry analysis were used collectively to accurately determine dissociation distance. Lastly, using high-resolution energy dispersive X-ray spectroscopy, no ordering or segregation was observed, indicating that this alloys is a true solid solution down to the atomic scale in the recrystallized and lightly deformed state. Graphical abstract: